(untitled) (Research, Society and Development, 2022)
Introduction: In January, 2020, WHO declared the new coronavirus as a public health emergency of international concern, later declared as a pandemic. As a strategy of dealing and of protection of susceptible people, vaccination has been adopted as the most efficient way of prevention, beyond the production of a lasting immunity to those vaccinated. Main goal: To annalyse COVID-19 vaccination coverage in pregnant women in an USF in the city of Maceió, from 2021 to 2022. Method: This is a retrospective, descriptive, epidemiological study, with a quantitative approach based on informations obtained from the local vaccination registration system report, concerning to the amount of doses applied of the COVID-19 vaccine in an USF in the city of Maceió, from 2021 to 2022. Results/Discussion: It is possible to check that there was a weak vaccine coverage in this period, which means a high risk of developing serious morbidity and mortality related to the infection by SARS-CoV-2. Conclusion: Vaccination is an individual and collective responsibility, therefore, new strategies must be taken by the health centers, in order to actively search for the missing pregnant women, or that have abandoned by half their vaccination schedule, as well as those who resist to the vaccination, as an attempt of increasing the number of pregnant women with their completed vaccination programme.